2D-silica ring interactions with alpha olefin sulphonate (AOS) surfactant under AOS/water system using molecular dynamic simulation / Nik Salwani Md Azmi... [et al.] - Md Azmi, Nik Salwani; Abu Bakar, Noor Fitrah; Megat Abdullah, Megat Ariff; Abd Latif, Abd Hafiz; Tengku Mohd, Tengku Amran (Universiti Teknologi MARA Shah Alam, 2019)
Molecular dynamic simulation of 2D silica and modified silica ring interaction with water/ alpha olefin sulfonate (AOS) was conducted and the interfacial tension as well as diffusion coefficient was predicted through the analysis. The simulation was performed using Material Studio software by assuming the silica nanoparticles as a 2D structure that represents a ring-like shape. The modified 2D silica ring was attached to hexyl-trimethoxysilane (HTMS) to create more hydrophobic structure on the silica surface. The analysis of the mean square displacement (MSD) shows that the diffusion of AOS molecules in the system with modified 2D silica ring were higher than unmodified silica ring which were 0.3099 Å2 /ps and 0.2891 Å2 /ps, respectively. The surface tension for the system after 100 ps with modified 2D silica ring was also lower than surface tension for unmodified silica ring which were 1.80x1010 GPa and 2.39x1010 GPa, respectively.